Contribution of the paternal histone epigenome to the preimplantation embryo - Dodd, Ashton R.; Luense, Lacey J. (Frontiers in Cell and Developmental Biology, 2024)
The paternal germline contains a plethora of information that extends beyond DNA. Packaged within the sperm cell is a wealth of epigenetic information, including DNA methylation, small RNAs, and chromatin associated histone proteins and their covalently attached post-translational modifications. Paternal chromatin is particularly unique, as during the process of spermatogenesis, nearly all histones are evicted from the genome with only a small percentage retained in the mature sperm cell. This paternal epigenetic information is encoded into chromatin during spermatogenesis and is delivered to the oocyte upon fertilization. The exact role of these paternally contributed histones to the embryo remains to be fully understood, however recent studies support the hypothesis that retained sperm histones act as a mechanism to poise genes for early embryonic gene activation. Evidence from multiple mammalian species suggests sperm histones are present at loci that are important for preimplantation embryo chromatin dynamics and transcriptional regulation. Furthermore, abnormal sperm histone epigenomes result in infertility, poor embryogenesis, and offspring development. This mini-review describes recent advances in the field of paternal histone epigenetics and their potential roles in preimplantation embryo development.